2022
DOI: 10.3390/life12040600
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Mean of Medical Visits Due to Psychiatric Disease in Korean Children and Adolescents before and during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has been suggested to have adverse impacts on psychiatric disorders. This study aimed to investigate the changes in medical visits due to a wide range of psychiatric disorders in children during the COVID-19 pandemic. The medical visits of all Korean children and adolescents (0–19 years old) due to the 12 following psychiatric disorders were investigated: autism; attention-deficit/hyperactivity disorder (ADHD); depressive disorder; bipolar disorder; primary insomnia; schizophrenia; panic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…7 , 11 , 12 It is known that suicidal symptomatology is very common in psychiatric setting and it is strongly associated with posttraumatic stress disorder (PTSD), dysthymia, and panic disorder diagnoses, 31 all conditions whose prevalence seemed to be significantly increased after the COVID-19 outbreak. 30 , 120 Compared to the pre-COVID-19 period, no statistically significant changes were observed for the suicidal outcomes in this specific setting, however an increase of 15% in suicidal ideation was reported by studies collecting 2020–2021 data (PR 1.15; 95% CI: 1.04–1.27). The same pattern could be observed also for suicidal behavior, without reaching the statistical significance.…”
Section: Discussionmentioning
confidence: 73%
“…7 , 11 , 12 It is known that suicidal symptomatology is very common in psychiatric setting and it is strongly associated with posttraumatic stress disorder (PTSD), dysthymia, and panic disorder diagnoses, 31 all conditions whose prevalence seemed to be significantly increased after the COVID-19 outbreak. 30 , 120 Compared to the pre-COVID-19 period, no statistically significant changes were observed for the suicidal outcomes in this specific setting, however an increase of 15% in suicidal ideation was reported by studies collecting 2020–2021 data (PR 1.15; 95% CI: 1.04–1.27). The same pattern could be observed also for suicidal behavior, without reaching the statistical significance.…”
Section: Discussionmentioning
confidence: 73%
“…Given the tremendous economic impact of the COVID-19 pandemic, its influence on adolescents should also be examined in detail. Youth mental health has already been found to have deteriorated in many countries due to the COVID-19 pandemic [ 36 ], and the rate of adolescent psychiatric treatment was found to have increased after the start of the COVID-19 pandemic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to an Australian report on adolescents, health anxiety (along with other psychopathology and mental health indicators) was high during the COVID‐19 pandemic when compared with normative data (Li et al., 2022). In a Korean study examining health insurance data on all Korean children and adolescents, most mental disorders, including hypochondriasis, were more often diagnosed in youths during the first year after the COVID‐19 outbreak compared to the year before (Kim et al., 2022). Conversely, a study from Denmark on children in middle childhood found low levels of health anxiety in the midst of the COVID‐19 pandemic; furthermore, those who did exhibit substantial health anxiety were likely to also have high anxiety levels prior to the pandemic (Hulgaard et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…According to an Australian report on adolescents, health anxiety (along with other psychopathology and mental health indicators) was high during the COVID-19 pandemic when compared with normative data (Li et al, 2022). In a Korean study examining health insurance data on all Korean children and adolescents, most mental disorders, including hypochondriasis, were more often diagnosed in youths during the first year after the COVID-19 outbreak compared to the year before (Kim et al, 2022).…”
Section: Societal Consequences and Influencesmentioning
confidence: 99%